HEALTHCARE FINANCING: THE NEXUS BETWEEN ENTREPRENEURIAL SUPPLY CHAIN PRACTICES AND PERFORMANCE OF PUBLIC HOSPITALS IN KENYA - Ndung’u, Ms. Hellen Njeri; Njeru, Dr. Duncan Mugambi; Muathe, Prof. Stephen Makau; Ocharo, Dr. Kennedy Nyabuto (South Eastern European Journal of Public Health, 2025)
The Vision 2030 development blueprint aspires to promote good health and well-being to all Kenyans. To support this, the Government of Kenya has instituted various reforms aimed at achieving good health. However, despite these reforms, there exists poor performance in the public hospitals in Kenya. To ensure effective, efficient, financially viable, and relevant service delivery, the entrepreneurial supply chain is critical, in public hospitals. Therefore, the study focused on Entrepreneurial Supply Chain practices, healthcare financing, and the performance of public hospitals in Kenya. Specifically, the study investigated the effect of innovative inventory management on the performance of public hospitals in Kenya, the influence of proactive strategic sourcing on the performance of public hospitals in Kenya, and the effect of risk-taking on the performance of public hospitals in Kenya. The study also sought to establish the moderating effect of healthcare financing on the relationship between entrepreneurial supply chain practices and the performance of public hospitals in Kenya. The study was guided by resource orchestration, resource dependency, and Schumpeterian innovation theories. The study adopted a positivism philosophy and utilised descriptive and explanatory research designs. The study's target population was 243 public hospitals in Kenya. The sample size was 151 public hospitals selected through proportionate sampling and simple random sampling techniques. The study utilised primary data collected through a semi-structured questionnaire. The validity of the questionnaire was checked using face and content analysis from the supervisors and experts who work in public hospitals; while reliability was checked through the use of Cronbach Alpha. A coefficient value of 0.7 was acceptable. Both descriptive and inferential statistics were used for data analysis. The study used multiple linear regression analysis to establish the relationship between the independent and dependent variables and the results obtained were expressed using tables and figures. The study findings revealed that innovative inventory management (β = 0.291; P-Value < 0.05), proactive strategic sourcing (β = 0.645; P-Value < 0.05), and risk taking (β = 0.313; P-Value < 0.05) have a positive and statistically significant relationship with the performance of public hospitals in Kenya. The study revealed a statistically significant (F=89.18, Sig<0.005) moderating effect of healthcare financing on the relationship between entrepreneurial supply chain practices and performance of public hospitals in Kenya. The study concluded that the adoption of entrepreneurial supply chain practices improves performance of public hospitals and therefore recommends the Chief Executive Officers and Medical Superintendents of public hospitals to adopt innovative inventory management, proactive strategic sourcing and risk taking entrepreneurial supply chain practices will provide insights into the management of public hospitals on entrepreneurial supply chain practices as they promote healthcare service delivery, reduce operational costs, enhance hospital reputation and increase effectiveness. The study recommends the Ministry of Health, Social Health Authority, Treasury and County Executive Committee member for Health in the County Governments to institute policies and reforms that promote sustainable financing of healthcare. Such initiatives include vigorous risk pooling through social insurance schemes and selling of health bonds. This will ultimately reduce overdependence on donor funding.